2016
DOI: 10.1371/journal.pone.0144885
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genomic Characterization of Vibrio mimicus Isolated from a Frozen Shrimp Processing Facility in Mexico

Abstract: Vibrio mimicus is a gram-negative bacterium responsible for diseases in humans. Three strains of V. mimicus identified as V. mimicus 87, V. mimicus 92 and V. mimicus 93 were isolated from a shrimp processing facility in Guaymas, Sonora, Mexico. The strains were analyzed using several molecular techniques and according to the cluster analysis they were different, their similarities ranged between 51.3% and 71.6%. ERIC-PCR and RAPD (vmh390R) were the most discriminatory molecular techniques for the differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…It can be isolated from a large number of environmental sources such as fresh, brackish and sea water (Campos et al., ; Guardiola‐Avila et al., ). V. mimicus has been linked to foodborne illnesses in recent years causing sporadic cases of diarrhoea with cholera‐like signs (Guardiola‐Avila et al., ). Phenotypically, most features of V. mimicus are identical to those found in V. cholerae , but it differs in its negative reactions to sucrose, Voges‐Proskauer, corn oil and Jordan tartrate (Boyd et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be isolated from a large number of environmental sources such as fresh, brackish and sea water (Campos et al., ; Guardiola‐Avila et al., ). V. mimicus has been linked to foodborne illnesses in recent years causing sporadic cases of diarrhoea with cholera‐like signs (Guardiola‐Avila et al., ). Phenotypically, most features of V. mimicus are identical to those found in V. cholerae , but it differs in its negative reactions to sucrose, Voges‐Proskauer, corn oil and Jordan tartrate (Boyd et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Nine genomes of V. mimicus were analyzed in this study. The genomes of V. mimicus CAIM-602 T (Vm602, PRJNA179483) [ 7 ], V. mimicus CAIM-1882 (Vm1882, PRJNA219179), V. mimicus CAIM-1883 (Vm1883, PRJNA219181) [ 20 ], and V. mimicus ATCC-33654 (Vm 33654, PRJNA231624) were sequenced by our research group, as previously reported [ 7 , 20 ]. The remaining five genomes sequences were obtained from the database of the National Center for Biotechnology Information (NCBI): V. mimicus MB451 (Vm451, PRJNA40509), V. mimicus VM223 (Vm223, PRJNA40483), V. mimicus VM603 (Vm603, PRJNA40241), V. mimicus VM573 (Vm573, PRJNA40243), and V. mimicus SX-4 (Vm SX4, PRJNA47421) [ 6 , 10 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The contigs were assembled with Geneious R6 ver. 6.0.3 (Biomatters Ltd. Auckland, New Zealand) to obtain the two chromosomes (ChI and ChII) of all V. mimicus strains [ 20 ]. The nine assembled sequences of each chromosome of V. mimicus strains and their corresponding counterparts of V. cholerae strains were aligned using progressiveMAUVE ver.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infective dose is unknown, but it is believed to be the same as that of V. cholerae , ranging from 10 4 to 10 6 cells [ 3 ]. This bacterium has been isolated from water and a variety of fishery products, such as oysters, sea turtle eggs, shrimp, crab, and fish [ 4 ].…”
Section: Introductionmentioning
confidence: 99%